2011
DOI: 10.1021/am200375a
|View full text |Cite
|
Sign up to set email alerts
|

Lubricant Degradation and Related Wear of a Steel Pin in Lubricated Sliding Against a Steel Disc

Abstract: In lubricated sliding contacts, components wear out and the lubricating oil ages with time. The present work explores the interactive influence between lubricant aging and component wear. The flat face of a steel pin is slid against a rotating steel disk under near isothermal conditions while the contact is immersed in a reservoir of lubricant (hexadecane). The chemical changes in the oil with time are measured by vibrational spectroscopy and gas chromatography. The corresponding chemistry of the pin surface i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Distinct C groups have been detected from the tribofilm. As seen from the C 1s spectra, the peaks at 284.5, 284.9, 285.1, and 285.5 eV corresponding to CC, CC, CH, CN bands are identified, whereas the peaks at 286.2 and 288.4 eV correspond to CO and CO bands . The presence of CO and CO bands indicates that thermal pyrolysis of PI and reaction of PI with O 2 or water vapor in atmosphere occur.…”
Section: Resultsmentioning
confidence: 92%
“…Distinct C groups have been detected from the tribofilm. As seen from the C 1s spectra, the peaks at 284.5, 284.9, 285.1, and 285.5 eV corresponding to CC, CC, CH, CN bands are identified, whereas the peaks at 286.2 and 288.4 eV correspond to CO and CO bands . The presence of CO and CO bands indicates that thermal pyrolysis of PI and reaction of PI with O 2 or water vapor in atmosphere occur.…”
Section: Resultsmentioning
confidence: 92%
“…Nascent metal surfaces are believed to be much more chemically active than oxidized surfaces and are both reactive with lubricants and act as catalyst in various chemical reactions. 17 (3) Wear debris . 24 Although less active than nascent metal surface, wear debris are also considered an effective catalyst in the chemical breakdown of lubricants.…”
Section: Resultsmentioning
confidence: 99%
“…The transformation of molecular structures is detrimental to the performance of lubricating oils . Many studies have investigated the oxidation of hydrocarbon oils, and the free‐radical chain oxidation mechanism has been proposed . However, the oxidation process of ester linkages is different to that of hydrocarbons due to their unique characteristics, and the oxidation mechanism of hydrocarbon oils does not satisfactorily explain the oxidation of synthetic ester oils.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Many studies have investigated the oxidation of hydrocarbon oils, and the free-radical chain oxidation mechanism has been proposed. [8][9][10][11][12] However, the oxidation process of ester linkages is different to that of hydrocarbons due to their unique characteristics, [13][14][15] and the oxidation mechanism of hydrocarbon oils does not satisfactorily explain the oxidation of synthetic ester oils. Several studies have reported structures of degradative products of diesters, whereas the structural details of polymerized products resulting from oxidation, as well as the polymerization mechanism, remain unclear.…”
Section: Introductionmentioning
confidence: 99%